Air Pollution and Breast Cancer in Iranian Women Living in Tehran Metropolis - Minaee, Farima; Sohrabi, Mohammad reza; Heidarnia, Mohammad Ali; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Cancer Biology, 2017)
Objective: This study aimed to evaluate the possible association between air pollution and breast cancer in women living in polluted urban area Methods: A frequency (five years age group) matching case-control study was conducted among women living Tehran Metropolis. Ambient carbon dioxide (CO2) as an indicator of exposure to air pollution and particulate matter 10 (PM10) as a carcinogen were used as exposure. Concentrations of the two indicators for the residential address of cases and control for the last five years were obtained from office of Tehran Air Quality Control Bureau (TAQB). All subjects were interviewed by phone and information about other risk factors (hormonal, behavioral anthropometric, and socio-economics) were obtained. Multivariate logistic regression model was used to estimate the odds ratios adjusted for confounding variables. CO2 entered into in the model as a continuous variable and PM10 was categorized as PM10 ≤ 1 VS 1 < PM10. Results: A total of 300 cases and 270 controls participated in the study. The mean age for cases and controls were 51.93 and 51.45 years, respectively. The distribution of air pollution throughout the study area indicated a large variation from a minimum of zero (no detectable) to a value of 16165.2612 µg/m3 for CO2. This figures were 0.03441 to 8.3242 µg/m3 for PM10. In average cases tend to live in areas with higher pollution indicators than controls PM10 was (PM10 < 1 µg/m3 = 107), (1 < PM10 <2 µg/m3 = 83) and (PM10 > 2 µg/m3 = 97) for cases and (PM10 < 1 µg/m3 = 108), (1 < PM10 < 2 µg/m3 = 87) and (PM10 > 2 µg/m3 = 105) for controls. Also CO2 index was a significant different with control groups as mean was (3943.87±3.50 µg/m3) for controls and (3199.84±2.72 µg/m3) for cases (P-value= 0.03). logCO2 as general indicator of exposure to air pollution was not observed association with breast cancer (OR = 1.218 and CI 95% 1.000 to 1.000). subjects in the case and control groups had no signific nt difference in terms of the level of PM10 index (OR = 1.047 and CI 95% 1.005 to 7.278). Conclusion: According to the results of this study, risk of breast cancer increases in women with exposure to air pollution, which denotes air pollution as a potential risk factor of breast cancer.